The Effect Of Traditional Games Hitam-Hijau On Achievment Sprint of 4th Grade Of Elementary School Bareng VI Jombang Year 2014/2015 - Arbiansyah, Avif (STKIP PGRI Jombang, 2013)
Â The purpose of this research are: to know the influence of hitam hijau game against the achievement of sprint (30 meters) Elementary School 4th grade students Bareng VI, and to know how much influence hitam hijau game against the achievement of sprint (30 meters) Elementary School 4th grade students Bareng VI.This study uses True Experimental Design with pretest and posttest. Learning to use a hitam hijau game approach as independent variables and achievement sprint (30 meters) of students as the dependent variable. The population was all students of 4th grade of Elementary School Bareng VI. Samples were 4th grade students were taken using random sampling techniques, and were divided into two groups: the experimental group were 12 students and a control group consisting of 11 students. Achievement sprint (30 meters) was measured by using a test run a short distance (30 meters). As a prerequisite test normality test using Lilliefors test and homogeneity test using Fisher's exact test. Hypothesis test using t test scores with a significance level of 5%.Results of the study are: 1) there is a significant effect of hitam hijau game approach to the achievement of sprint (30 meters) students of Elementary School 4th grade Bareng VI, 2) the influence of hitam hijau game approach to the achievement of sprint (30 meters) students of Elementary School 4th grade Bareng VI is equal to 20.73%.Learning approach hitam hijau game indicates an active student involvement and making the teacher as a facilitator. Hitam hijau game given at each meeting of the core activities make students better understand the material being taught, thus increasing student achievement.